Two iterative channel estimation algorithms in single‐input multiple‐output (SIMO) LTE systems. Issue 1 (24th October 2012) - Liu, Yang; Sezginer, Serdar; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT Accurate channel estimation is a challenging problem in a long term evolution systems especially in highly selective channels. In this paper, two iterative channel estimation algorithms are proposed to efficiently estimate channels over the orthogonal frequency‐division multiplexing (OFDM) symbols containing pilot symbols. The first one is proposed based on a simple interpolation algorithm, named as simple iterative frequency interpolation (SIFI), and improves the system performances with low implementation complexity. The second one is derived from the traditional expectation maximisation (EM) algorithm in OFDM systems. In order to deal with the 'null' subcarriers in the guard band and make the algorithm converge, the truncated singular value decomposition method is integrated to truncated singular value decomposition expectation‐maximisation (TSVD‐EM). Both channel estimation algorithms are followed by a simple linear interpolation in time domain to obtain channel estimates over the whole subframe. Complexities of the proposed algorithms are also analysed and compared. Simulation results show that the SIFI algorithm outperforms the traditional interpolation method with a low complexity, and the TSVD‐EM algorithm approaches the best achievable performance with a reduced complexity.Copyright © 2012 John Wiley & Sons, Ltd.